2004
DOI: 10.1523/jneurosci.1144-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Visual Cortex in the Owl Monkey

Abstract: In this study, we compared the organization of orientation preference in visual areas V1, V2, and V3. Within these visual areas, we also quantified the relationship between orientation preference and cytochrome oxidase (CO) staining patterns. V1 maps of orientation preference contained both pinwheels and linear zones. The location of CO blobs did not relate in a systematic way to maps of orientation; although, as in other primates, there were approximately twice as many pinwheels as CO blobs. V2 contained band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
85
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 59 publications
25
85
0
Order By: Relevance
“…In owl monkeys, lesions and deactivations of V1 rendered MT unresponsive to visual stimuli (24,38). However, reanalysis of the orientation preference maps from our previous study revealed only a small and inconsistent overrepresentation of cardinal orientations in the region of V1 representing 0-10°eccen-tricity in owl monkeys, whereas more peripheral portions of V1 were unavailable for imaging (23). In the bush baby a consistent anisotropy was found in V1 by using optical imaging but only for the 0-3°representation and not beyond this eccentricity (X.X., T. J. Anderson, and V.A.C., unpublished observations).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…In owl monkeys, lesions and deactivations of V1 rendered MT unresponsive to visual stimuli (24,38). However, reanalysis of the orientation preference maps from our previous study revealed only a small and inconsistent overrepresentation of cardinal orientations in the region of V1 representing 0-10°eccen-tricity in owl monkeys, whereas more peripheral portions of V1 were unavailable for imaging (23). In the bush baby a consistent anisotropy was found in V1 by using optical imaging but only for the 0-3°representation and not beyond this eccentricity (X.X., T. J. Anderson, and V.A.C., unpublished observations).…”
Section: Discussionmentioning
confidence: 64%
“…As shown in Fig. 1 a-c, orientation domains in MT of owl monkeys were organized very much like those of V1 (23), with clear isoorientation domains ( Fig. 1 a and b) and continuous representation of a series of pinwheels and linear zones (Fig.…”
Section: Unequal Representation Of Cardinal and Oblique Orientations mentioning
confidence: 87%
See 3 more Smart Citations